2019
DOI: 10.3390/su11020493
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Wood-Based Energy: Evaluation and Strategies for Mainstreaming Sustainability in the Sector

Abstract: Bioenergy, mostly from wood biomass, is now widely seen as an important element in the efforts to tame dangerous climate change. At the same time, foresters and development specialists note that wood-based energy production can contribute to rural development. However, to deliver on these two goals without generating negative side effects, wood-based energy has to be sustainable, while currently, the sector is developing rapidly in ways that are technologically advanced, with questionable sustainability. How c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…The authors who analyzed the use of these integrated approaches by companies, in particular with reference to environmental protection initiatives (Szulecka, 2019;Ramos, 2019;Brack et al, 2019;da Silva and Prasad, 2019;Hölscher et al, 2018;Neto, 2016;Nikolaou et al, 2015;Atkins et al, 2015;Butler et al, 2014), have shown that organizations are better prepared to develop strategies to contain the associated risks of company activities. This Concise bibliometric analysis causes an improvement in reputation and a reduction in costs associated with policies in recognition of climate change (Elder et al, 2016).…”
Section: Years 2011-2020mentioning
confidence: 99%
“…The authors who analyzed the use of these integrated approaches by companies, in particular with reference to environmental protection initiatives (Szulecka, 2019;Ramos, 2019;Brack et al, 2019;da Silva and Prasad, 2019;Hölscher et al, 2018;Neto, 2016;Nikolaou et al, 2015;Atkins et al, 2015;Butler et al, 2014), have shown that organizations are better prepared to develop strategies to contain the associated risks of company activities. This Concise bibliometric analysis causes an improvement in reputation and a reduction in costs associated with policies in recognition of climate change (Elder et al, 2016).…”
Section: Years 2011-2020mentioning
confidence: 99%
“…For example, it has been proposed to replace a substantial fraction of fossil fuels, as an energy source, by burning biomass (Tursi 2019). The argument has been made that such practices can be carried out in a sustainable manner (Szulecka 2019). Trees used as fuel can regrow, assuming that a healthy forest system is maintained.…”
Section: Climate Changementioning
confidence: 99%
“…It may differ from the final official version of record. replace fossil fuel-based energy could reinforce the forest sector and at the same time promote climate change mitigation (Sacchelli et al 2013;Lewandowski 2015;Szulecka 2019). Biodiversity conservation strongly supports adaptive management strategies (Klenk et al 2015;Isbell et al 2015).…”
Section: Csf Trend From 1990 To 2015mentioning
confidence: 99%